(untitled) (Bangladesh Journal of Nutrition, 2015)
An enzymatic-gravimetric method was employed to determine the content of insoluble dietary fiber and lignin in 4 cereals, 5 pulses, 4 starchy roots, and 3 tubers along with some of their varieties. The cultivars were identified at Bangladesh Agriculture Research Council and noted as their high yielding varieties released within last decade for cultivation in Bangladesh. Insoluble dietary fiber content, equivalent to alpha-amylase treated neutral detergent fiber (termed as E-NDF), was in a range from 0.97 g to 10.45 g for cereals, 8.18 g to 25.66 g for pulses, 2.62 g to 6.88 g for roots, and 2.26 g to 8.11 g for tubers per 100 g raw sample. Cell wall polysaccharides and Lignin were estimated from the E-NDF fraction sequentially using the methods of Van Soest and co-workers. Hemicellulose was found dominant among cell-wall polysaccharides in all the studied materials (up to 24.85% in pulses). Cell wall polysaccharide and lignin were not detected in some of the studied samples. Highest amount of cellulose was found in ’Gourab’ variety of wheat (3.48%) while highest amount of lignin was estimated in sweet potato (2.87%). The results will, thus, provide a source data for dietary calculations.